2012
DOI: 10.1124/mol.112.079707
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Regulation of Murine Cardiomyocyte Contractility by Nanomolar (−)-Epigallocatechin-3-Gallate, the Major Green Tea Catechin

Abstract: Green tea polyphenolic catechins exhibit biological activity in a wide variety of cell types. Although reports in the lay and scientific literature suggest therapeutic potential for improving cardiovascular health, the underlying molecular mechanisms of action remain unclear. Previous studies have implicated a wide range of molecular targets in cardiac muscle for the major green tea catechin, (Ϫ)-epigallocatechin-3-gallate (EGCG), but effects were observed only at micromolar concentrations of unclear clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Nevertheless, 1.8 μM EGCg reduced relaxation time, and this effect was more prominent in KI cells, whereas the effects on diastolic Ca 2+ and Ca 2+ kinetics did not differ between the genotypes. The increase in diastolic Ca 2+ could be explained by an inhibiting effect on the Na + /Ca 2+ exchanger (NCX), as reported with 10 nM (Feng et al, 2012) and 2.5 μM (Lorenz et al, 2008). The faster time to peak Ca 2+ is probably due to EGCg effects on the ryanodine receptor.…”
Section: Discussionmentioning
confidence: 58%
“…Nevertheless, 1.8 μM EGCg reduced relaxation time, and this effect was more prominent in KI cells, whereas the effects on diastolic Ca 2+ and Ca 2+ kinetics did not differ between the genotypes. The increase in diastolic Ca 2+ could be explained by an inhibiting effect on the Na + /Ca 2+ exchanger (NCX), as reported with 10 nM (Feng et al, 2012) and 2.5 μM (Lorenz et al, 2008). The faster time to peak Ca 2+ is probably due to EGCg effects on the ryanodine receptor.…”
Section: Discussionmentioning
confidence: 58%
“…In both genetic and environmental models of heart disease, utilizing this protocol provides key information about cell contractility, sarcomeric contractility and relaxation, calcium transients, and cytoskeletal disruption. This system is often used to test the effect of drugs on isolated cardiomyocytes 6,7 . We employ the system to compare contractility and calcium transients of cardiomyocytes between wild type mice and mice with a mutation leading to dilated cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Isolation and physiological analysis of myocytes have been used by countless labs for a variety of experiments including studying the effect of drugs 6,7 [15][16][17] . With the application of any of these stressors, changes in heart function could be due to any combination of changes in the cardiomyocytes themselves and changes in the surrounding environment of the heart, such as scarring, changes in conductivity, or changes to the extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%
“…This permits the conclusion that both lipid NPs are highly stable systems and can be considered suitable carriers for the oral administration of EGCG, avoiding the premature release of EGCG in simulated gastric and intestinal conditions and allowing a controlled release after the absorbance into the bloodstream. Finally, the in vitro viability and cytotoxicity studies revealed that the formulations were biocompatible, and the obtained IC 50 is far superior to the reported therapeutic concentrations 2022…”
Section: Resultsmentioning
confidence: 93%